2008
DOI: 10.1016/j.biomaterials.2007.08.050
|View full text |Cite
|
Sign up to set email alerts
|

Iron oxide nanoparticles as a drug delivery vehicle for MRI monitored magnetic targeting of brain tumors

Abstract: This study explored the possibility of utilizing iron oxide nanoparticles as a drug delivery vehicle for minimally invasive, MRI-monitored magnetic targeting of brain tumors. In vitro determined hydrodynamic diameter of ~100nm, saturation magnetization of 94 emu/g Fe and T 2 relaxivity of 43 s −1 mM −1 of the nanoparticles suggested their applicability for this purpose. In vivo effect of magnetic targeting on the extent and selectivity of nanoparticle accumulation in tumors of rats harboring orthotopic 9L-glio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
526
0
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 806 publications
(550 citation statements)
references
References 41 publications
11
526
0
4
Order By: Relevance
“…Chertok et al observed that a magnetic force of 0.4 T increased the concentration of starch-coated SPIONs (∼110 nm) targeted toward a rat brain tumor by 11.5-fold over the concentration found in nontargeted (no magnetic force applied) brain tumors. 13 Similar results have been shown for starch-coated SPIONs with a diameter of 46 nm that were intravenously injected into nude mice with tumor xenografts. 31,32 The SPIONs were shown to accumulate at a higher concentration in the tumors when they were subjected to an external magnetic field of 0.5 T. 31,32 These studies all refer to magnetic force-increased delivery of SPIONs in tumor tissue that is known to have a compromised blood−tumor barrier.…”
Section: ■ Results and Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…Chertok et al observed that a magnetic force of 0.4 T increased the concentration of starch-coated SPIONs (∼110 nm) targeted toward a rat brain tumor by 11.5-fold over the concentration found in nontargeted (no magnetic force applied) brain tumors. 13 Similar results have been shown for starch-coated SPIONs with a diameter of 46 nm that were intravenously injected into nude mice with tumor xenografts. 31,32 The SPIONs were shown to accumulate at a higher concentration in the tumors when they were subjected to an external magnetic field of 0.5 T. 31,32 These studies all refer to magnetic force-increased delivery of SPIONs in tumor tissue that is known to have a compromised blood−tumor barrier.…”
Section: ■ Results and Discussionsupporting
confidence: 72%
“…Chertok et al found that the concentration of SPIONs dispersed into normal brain tissue of Fischer 344 rats seemed to increase slightly (∼3-fold) under the influence of a magnetic field (0.4 T) versus that of non-magnetic-force-targeted SPIONs. 13 Also, the migration of monocytes loaded with magnetic liposomes has been shown to be enhanced 3-fold via application of a magnetic force in an in vitro BBB model. 17 The amount of polystyrene-entrapped magnetic nanoparticles found in the brain tissue of 10-week-old mice after systemic delivery was increased by 25-fold with the aid of an external magnet with a strength of ∼1 T. 27 In this study, the extent of passage of SPIONs across an in vitro BBB was clearly increased manyfold by a magnetic force.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The contrast agent is then measured directly, and drug delivery is determined based on its concentration on the contrast agent (12,13). The second method assesses therapeutic agent delivery to the brain more accurately, and SPIO nanoparticles have many advantages in this regard: (i) SPIO nanoparticles are biocompatible and can be degraded safely by macrophages/ microglia (14), whereas gadolinium leakage raises safety concerns related to neurotoxicity (15); (ii) SPIO nanoparticle surfaces can be modified to easily conjugate therapeutic agents (12,13); (iii) MRI techniques such as T 2 *-weighted imaging or transverse relaxation rate (R 2 ) maps can be used to quantify the iron concentration in tissues, making quantification of therapeutic agent delivery easier (12,13); (iv) SPIO nanoparticles have high spin-spin relaxivities and can generate high magnetic moments that can be actively manipulated by externally applied magnets, making them suitable for use with magnetic targeting (16,17). The above advantages makes the SPIO nanoparticles has the potential to serve a ''thernostic'' agent, which means that the diagnostic and therapeutic functions can be concurrently provided during drug-delivering process.…”
mentioning
confidence: 99%